Legal Challenges in Hospital Management and Their Impact on the Quality of Healthcare - Ezzerouali , Souad; Al-Hadrawi, Baqer Khudair; Al-hadrawi, Kais Khudhair; Mahroug, Mohamed; Alhadrawi, Ali Khudayer Abdulabbas; Aldhalmi, Hanan Khaled (Journal of Ecohumanism, 2024)
Legal issues present significant challenges to healthcare quality by introducing barriers such as regulatory compliance requirements, conflicts over patient rights, and medical malpractice risks. These challenges often lead to increased operational costs, higher litigation risks, and diminished patient trust. This study examines how hospital administrators can effectively manage legal risks related to healthcare laws, identifying strategies to mitigate these challenges to improve healthcare quality and patient satisfaction while minimizing legal disputes. The research evaluates existing legal frameworks, reviews case studies of legal disputes in healthcare, and analyzes risk management practices adopted by administrators. Findings highlight that implementing legal compliance systems, providing staff training on relevant laws, and fostering collaboration with legal experts are critical strategies. These measures not only reduce risks of litigation but also enhance operational efficiency and bolster patient trust. By addressing the intersection of legal theory and healthcare practice, the study offers actionable recommendations for healthcare institutions. It underscores the importance of proactive legal risk management in improving service delivery, institutional reputation, and patient outcomes.